PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PADA SKPD KABUPATEN ACEH UTARA - Indana Zulfah; Sri Wahyuni; Arina Nurfaza (LPPM STIE Lhokseumawe, 2017)
This study on the effect of accounting information system on the quality of the financial statements in North Aceh regency SKPD. The purpose of this study is toexamine the effect of the accounting information system on the quality of the financial statements in North Aceh regency SKPD. The data used in this study are primary data by dividing the questionnaire to 98 employees whose serve as research samples. The data processing is done with the help of a simple linear equation model of SPSS. The results showed that: The accounting information system has a strong relationship with the quality of financial reporting in North Aceh regencySKPD . Accounting information system has the ability to explain the effect on the quality of financial reporting in North Aceh regency SKPD.